Acute hypotensive and diuretic activities of Berberis vulgaris root bark aqueous extract in normal rats - Muhammad Ahmed; Aisha Azmat; Salahuddin Khan (Universidade de São Paulo, 2018)
ABSTRACT The aim of this study is to investigate the effectiveness of intravenous administration of Berberis vulgaris root bark aqueous extract (BRBD) on the cardiovascular and renal functions of healthy normotensive rats. The different doses of BRBD 1, 10 and 20 mg/kg were administered intravenously (i.v) in normal rats. Blood pressure, diuretic activity and serum renal profile were analyzed. Intravenous injection of BRBD at the different doses of 1, 10 and 20 mg/kg showed a dose-dependent reduction in mean arterial blood pressure (P<0.001). At different doses of 1, 10 and 20 mg/kg, the hypotensive effect remained for more than one hour. Single dose administration of BRBD at doses of 10 and 20 mg/kg caused a significant increase in urine output (P<0.001) as compared to the control rats. Serum renal profile test (albumin, Urea, Uric Acid, creatinine and BUN) did not show any significant alteration. The authors conclude that the BRBD is a potent hypotensive and possesses diuretic potential